2021
DOI: 10.1002/smi.3090
|View full text |Cite
|
Sign up to set email alerts
|

Associations of childhood and adult adversity with daily experiences in adulthood

Abstract: Data from 213 adults were analysed to test the stress accumulation and stress sensitization models as they relate to daily mood, health behaviours and social interactions. Adults reported on childhood adversity, past year adversity, and daily experiences on 14 evenings. Results largely supported the stress accumulation and not stress sensitization model such that childhood and past year adversity had independent but not synergistic effects on daily experiences. Both adversity measures were independently associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 55 publications
(92 reference statements)
0
4
0
Order By: Relevance
“…The RFQ has been validated against clinical interviews of childhood adverse experiences (e.g., Taylor et al, 2004) and demonstrated good internal consistency (Cronbach’s α ranges from .77 to .85; Coelho et al, 2014). Previous research analyzing the PCS3 data have reported Cronbach’s α = .72 (Nayman et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…The RFQ has been validated against clinical interviews of childhood adverse experiences (e.g., Taylor et al, 2004) and demonstrated good internal consistency (Cronbach’s α ranges from .77 to .85; Coelho et al, 2014). Previous research analyzing the PCS3 data have reported Cronbach’s α = .72 (Nayman et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…The RFQ has been validated against clinical interviews of childhood adverse experiences and demonstrated good internal consistency (Cronbach’s α ranges from 0.77–0.85) [ 35 , 36 ]. Previous research analyzing the PCS3 data have reported Cronbach’s α = 0.72 [ 37 ]. For the purposes of this study, higher total RFQ scores will be considered to reflect more stressful, less supportive early environments.…”
Section: Methodsmentioning
confidence: 99%
“…Research on childhood adversity indicates that childhood adversity is associated with higher negative affect, lower positive affect (56,57) and higher perceived stress (58) during daily life in adult non-clinical samples, and with the development of various forms of psychopathology (cf. 26,59).…”
Section: Effects Of Childhood Adversitymentioning
confidence: 99%